2022
DOI: 10.1002/deo2.146
|View full text |Cite
|
Sign up to set email alerts
|

Linked color imaging improves the diagnostic accuracy of eosinophilic esophagitis

Abstract: Objectives To assess the usefulness of linked color imaging (LCI), a recently developed image‐enhanced endoscopy technique, in the endoscopic diagnosis of eosinophilic esophagitis (EoE). Methods Thirty white light images (WLIs) and 30 WLI+LCI images collected from patients with and without EoE were randomly and blindly reviewed by 10 endoscopists, including four experts (Exs) and six non‐Exs. Edema, ring, exudate furrows, and strictures were rated on the adjusted EoE en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…The optimal cutoff value for the ERERS score to predict EoE has not been determined. Some reports showed that an EREFS ≥ 2 can predict EoE with relatively high sensitivity and specificity [ 38 , 48 ], while others suggested that it was not sufficient to discriminate between EoE and non-EoE, due to low specificity against high sensitivity [ 49 ]. This discrepancy may be due to differences in the endoscopic severity of the EoE group enrolled in each study, and the clinical profiles of the non-EoE comparative groups.…”
Section: Eoe Endoscopic Reference Score (Erefs)mentioning
confidence: 99%
See 2 more Smart Citations
“…The optimal cutoff value for the ERERS score to predict EoE has not been determined. Some reports showed that an EREFS ≥ 2 can predict EoE with relatively high sensitivity and specificity [ 38 , 48 ], while others suggested that it was not sufficient to discriminate between EoE and non-EoE, due to low specificity against high sensitivity [ 49 ]. This discrepancy may be due to differences in the endoscopic severity of the EoE group enrolled in each study, and the clinical profiles of the non-EoE comparative groups.…”
Section: Eoe Endoscopic Reference Score (Erefs)mentioning
confidence: 99%
“…In a more recent Japanese study, interobserver and intraobserver agreement have been reported to increase to 0.60 and 0.74 for WLI, respectively. This might reflect an increasing awareness of EoE [ 48 ]. The comparison between original EREFS and expanded EREFS by Ma et al does not show a significant difference in the diagnostic agreement regarding each endoscopic finding [ 36 ].…”
Section: Diagnostic Agreement Of Endoscopic Findings and Diagnosismentioning
confidence: 99%
See 1 more Smart Citation
“…This technology is based on the combination of four types of light as source emitters: blue-violet, blue, green, and red. LCI is a recent development (Fujifilm Corporate) in imaging technology created by a short-wavelength narrowband laser light in combination with a white laser light, enabling a brighter light in distant areas with a higher contrast between white and red spots [ 6 ]. BLI and LCI are two of the observation modes of the four-LED multi-light technology that allows enhanced visualization of hemoglobin by, respectively, intensifying the blue or red light spectrum, improving delineation and detection [ 7 , 8 , 9 ].…”
Section: Advanced Endoscopic Imaging Technologies For Detection and M...mentioning
confidence: 99%
“…Prior reports have found that LCI increases color differences and visibility in gastric cancer, colorectal neoplasia, and duodenal tumors [10][11][12][13][14]. Recently, LCI has also been found to be beneficial in the endoscopic detection of both neoplastic lesions and inflammatory lesions such as reflux esophagitis and eosinophilic esophagitis [15,16].…”
Section: Introductionmentioning
confidence: 99%